1999
DOI: 10.1034/j.1600-051x.1999.261004.x
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin in gingival crevicular fluid correlates with clinical and biochemical markers of periodontal disease

Abstract: Clinical and biochemical markers of periodontal disease have been used for precise objective diagnosis of periodontal inflammation. Interleukin 1beta (IL-1beta) and prostaglandin E2 (PGE2), inflammatory factors, levels in gingival crevicular fluid (GCF) of patients with periodontal disease are elevated and have been studied as biochemical markers. The levels of calprotectin, a leukocyte protein, in body fluids of patients with some inflammatory diseases are raised. Recently, we detected calprotectin in GCF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 27 publications
(39 reference statements)
7
94
1
2
Order By: Relevance
“…The present data indicated that GCF calprotectin levels increased as the periodontal disease progresses from health to disease, but similar in G-AgP and CP. Our findings are consistent with the previous data showing the role of calprotectin as an inflammatory marker of periodontal disease [11,12,42,43]. Kaner et al [44] have demonstrated that GCF calprotectin levels are significantly correlated with the levels of periodontal inflammation and decreased after periodontal therapy in G-AgP patients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The present data indicated that GCF calprotectin levels increased as the periodontal disease progresses from health to disease, but similar in G-AgP and CP. Our findings are consistent with the previous data showing the role of calprotectin as an inflammatory marker of periodontal disease [11,12,42,43]. Kaner et al [44] have demonstrated that GCF calprotectin levels are significantly correlated with the levels of periodontal inflammation and decreased after periodontal therapy in G-AgP patients.…”
Section: Discussionsupporting
confidence: 83%
“…Although this technique provides larger GCF volumes compared to superficial intracrevicular technique [40], in accor- dance with the suggestions of others our discussion of the data as well as studying relationship with clinical data was based on the total amount rather than concentration of the data which consider the amount of GCF collected [37,41]. The relationship between GCF calprotectin levels and several other inflammatory markers has been previously investigated and calprotectin levels were shown to be a significant contributor to host defense against infection [8,9,42,43]. The present data indicated that GCF calprotectin levels increased as the periodontal disease progresses from health to disease, but similar in G-AgP and CP.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we detected calprotectin in Gingival crevicular fluid and its concentrations in periodontal pockets were higher than those in healthy gingival crevices [16,17] . Investigations done by Jun-ichi Kido found the correlations between Gingival crevicular fluid calprotectin levels and clinical indicators (probing depth and bleeding on probing, BOP), and the IL-1β and PgE 2 levels [14] .…”
Section: Effect Site Change In Concentrationmentioning
confidence: 93%
“…Kido, J., Nakamura, T., Kido, R., Ohishi, K., Yamauchi, N., Kataoka, M., and Nagata, T. (1999). Calprotectin in gingival crevicular fluid correlates with clinical and biochemical markers of periodontal disease.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…It is expressed in neutrophils, monocytes, macrophages, and mucosal keratinocytes and is involved in leukocyte trafficking and arachidonic acid metabolism (Nacken et al, 2003). It is upregulated in inflammatory conditions, including periodontal disease in which it is elevated in the gingival cervicular fluid (Kido et al, 1999). It is constitutively expressed in cells of stratified oral epithelia and in cultured gingival epithelial cells and is highly responsive to stress in epidermis (Marionnet et al, 2003).…”
mentioning
confidence: 99%